Analisis Minat Nasabah Dalam Menggunakan Produk Gadai Rahn Pada PT. Bank Syariah Indonesia KCP Pangkalan Brandan - senja, Senja Nuansa Febryola (Peduli Riset dan Pengabdian Masyarakat, 2022)
This study focuses on the discussion of procedures and realization, customer interest and customer perceptions of rahn pawn products at PT. Bank Syariah Indonesia KCP Pangkalan Brandan. The research method used in this study is a descriptive qualitative research method with an empirical approach. Informants in this study were employees and customers using rahn pawn products at PT. Bank Syariah Indonesia KCP Pangkalan Brandan. The results of the study explain that the process and realization of rahn pawn products at PT. Bank Syariah Indonesia KCP Pangkalan Brandan is quite easy, that is, the customer fills out a customer financing request form, then the customer submits the mortgaged item to the pawn officer, then the appraiser determines the amount of financing to be received and the costs to be paid by the customer. Implementation of rahn pawn products at PT. Bank Syariah Indonesia KCP Pangkalan Brandan uses three contracts, namely qardh contract, rahn contract and ijarah contract. Several factors that influence the high public interest, namely service factors, promotion factors, religious factors. Customers have a good perception of the existence of rahn pawn products because the procedures and realization are easy, the costs are low, the transactions are in line with Islamic law and it makes it easier for customers to get capital to develop their business.